Facile and Direct Preparation of Ultrastable Mesoporous Silica with Silver Nanoclusters: High Surface Area. Issue 1 (17th January 2020) - Aqeel, Tariq; Bumajdad, Ali
Abstract: We report the successful direct synthesis of an ultrastable mesoporous silicon dioxide framework containing silver nanoclusters using a modified true liquid crystal templating method. Our modification produced an extraordinary material with a high average Brunauer‐Emmett‐Teller specific surface area of 1785 m 2 g −1 – the highest reported surface area to date – and an ultrastable mesoporous structure, which has been stable for nine years so far. This method eliminates the need for reduction of silver oxide into metallic silver and restricts the growth of silver clusters. The silver nanoclusters, with an average size of 1 nm, occupy the pores and walls of the framework. Analysis of the material using nitrogen adsorption/desorption method, high‐resolution transmission electron microscopy, X‐ray diffractometry, energy‐dispersive X‐ray diffractometry, X‐ray photoelectron spectroscopy, and scanning electron microscopy is discussed herein. Abstract : A decade of stability : A successful direct synthesis of a mesoporous silica framework containing 1‐nm silver nanoclusters using a modified true liquid crystal templating method. This method produced an extraordinary material with a high surface area and an ultrastable mesoporous structure that has been stable for nine years.